Blockwise Analysis of Health Indicators of Gadchiroli District using Composite Index: An application of GKG Algorithm - Gotmare, Anil D; Khot, P.G.; Gotmare, Shraddha R. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
Gadchiroli district is a part of Vidarbha, Traibal district away from 200 KM from sub capital of Maharashtra, Nagpur, Gadchiroli is well known tribal district of vidarbha. Total forest cover of the district is around 78% of total geographic area. District has 12 blocks with 6 revenue division. It is a notified tribal district having 8.61%–81.50% tribal population in different blocks and block-wise urbanization varies from 0.00% to 37.10%. Objective: Objective of present research paper is to device tool to rank the blocks of the district according to community health status exist in blocks and accordingly assess community health status at block level in Gadchiroli district.